Digital transformation of healthcare through the prism of trends, challenges and principles: Digitalna preobrazba zdravstva skozi prizmo trendov, izzivov in načel - Turkanović, Muhamed (Acta Medico-Biotechnica, 2023)
Based on the theoretical research method perspective, we present the complex topic of digitalizing the healthcare domain. We start withthe elaboration of the keywords connected to digitalization and continue with a slight overview of principles, trends, and challenges. Thepaper is limited only to the digital transformation processes and thus excludes insights into technology-related topics like nanomedicine,bioengineering, etc. While presenting the trends, we try to emphasize the key novel technologies currently being used to supporthealthcare digitalization endeavors. We conclude by highlighting the most important actions and initiatives (focusing on the EU market),which are and will be of high importance for the healthcare domain in the future.
Keywords: artificial intelligence, Data Spaces, digital health, digital transformation, digitalization, EHR